Effects of the Coastal Uplift on the Kuroshio Ecosystem, Eastern Taiwan, the Western Boundary Current of the North Pacific Ocean - Chen, Chung-Chi; Lu, Chun-Yi; Jan, Sen; Hsieh, Chih-hao; Chung, Chih-Ching (Frontiers in Marine Science, 2022)
The Kuroshio is the western boundary current of the North Pacific Ocean. In the subtropical region of eastern Taiwan, a coastal uplift of the isotherms has occurred. To explore its impact on this oligotrophic ecosystem, hydrographic data along the transect line at 23.75oN were measured between September 2012 and September 2014. Results show that the coastal uplift intensity is related to the water volume transport of the Kuroshio. The increase (or decrease) of isotherm slope (or the coastal uplift) across the Kuroshio was most likely associated with violation of the geostrophic balance. Significant dissolved inorganic nutrients have been uplifted to the sunlit zone, especially in the onshore. For example, compared to the offshore, nitrate concentration increased 0.49 μM in the upper 100 m of the onshore. The uplifted nutrients thereafter enhanced the growth of phytoplankton; for instance, its biomass could reach 2.03 µg Chl L-1 in the shallow water of an onshore station. Phytoplankton was mostly composed of picophytoplankton, which were dominated, in terms of relative abundance, by Prochlorococcus (83.6 %), followed by Synechococcus (13.8 %) and picoeukaryotes (2.7 %). Interestingly, the relative abundance of Prochlorococcus increased from onshore toward offshore, but the trend was reversed for Synechococcus and picoeukaryotes, which may be associated with the coastal uplift effect. This coastal uplift may play an important role in resolving the “Kuroshio paradox”. Its magnitude and impact may even be intensified due to global warming.